Modeling the Geometry of Plate Boundary and Seismic Structure in the Southern Ryukyu Trench Subduction Zone, Japan, Using Amphibious Seismic Observations. Issue 2 (28th February 2018) - Yamamoto, Y.; Takahashi, T.; Ishihara, Y.; Kaiho, Y.; Arai, R.; Obana, K.; Nakanishi, A.; Miura, S.; Kodaira, S.; Kaneda, Y.
Abstract: Here we present the new model, the geometry of the subducted Philippine Sea Plate interface beneath the southern Ryukyu Trench subduction zone, estimated from seismic tomography and focal mechanism estimation by using passive and active data from a temporary amphibious seismic network and permanent land stations. Using relocated low‐angle thrust‐type earthquakes, repeating earthquakes, and structural information, we constrained the geometry of plate boundary from the trench axis to a 60 km depth with uncertainties of less than 5 km. The estimated plate geometry model exhibited large variation, including a pronounced convex structure that may be evidence of a subducted seamount in the eastern portion of study area, whereas the western part appeared smooth. We also found that the active earthquake region near the plate boundary, defined by the distance from our plate geometry model, was clearly separated from the area dominated by short‐term slow‐slip events (SSEs). The oceanic crust just beneath the SSE‐dominant region, the western part of the study area, showed high V p / V s ratios (>1.8), whereas the eastern side showed moderate or low V p / V s (<1.75). We interpreted this as an indication that high fluid pressures near the surface of the slab are contributing to the SSE activities. Within the toe of the mantle wedge, P and S wave velocities (<7.5 and <4.2 km/s, respectively) lower than those observed through normal mantle peridotite might suggest that some portions of the mantle may be at least 40% serpentinized. Key Points: Interface geometry of subducted Philippine Sea Plate suggests the existence of subducted seamount Slow slips and normal interplate earthquakes are separately located along the plate boundary High fluid pressure within the oceanic crust is related to slow‐slip activity